Chronicle of the Colloquium "Sport and Business Law" at the University Toulouse 1 Capitole, France, on 11 October 2018. - Marine Lercier (Universitat Autonoma de Barcelona. Facultat de Dret, 2019)
On October 11, 2018, the Association of Doctors and Ph.D. Candidates of the Business Law Center (ADDCDA) organized at the University Capitole I, Toulouse, France, a Colloquium on the theme "Sport and Business Law" presented by its then President Tamara Dupuy and conducted under the aegis of the University of Toulouse 1 Professor Arnaud DE BISSY, Deputy Director of the Business Law Centre and Grégory SINGER, Doctor of Law, co-head of the Master in Sport Management at the University of Toulouse 1.